Root development of coconut reciprocal crosses and their parental cultivars at early bearing stage - Nuñez, Tessie C.; Lina, Dario P. (Annals of Tropical Research, 1998)
To understand the influence of parent coconut cultivars on the root development of their hybrid, this study was conducted in Inopacan, Leyte using eight dwarf and tall reciprocal crosses and their parent genotypes. Coconut crosses with dwarf (D) and tall (T) parents were found to have lighter roots than the tall parents but had heavier roots than the dwarf parents. Significant differences in root weight of reciprocal crosses were observed in some sampling points in specific cross combinations. However, these were not general trends for D x T and T x D crosses. Generally, crosses involving Baybay Tall had more roots which were distributed wider and deeper in the soil than crosses with Puringkitan as one of the parents.